After the boom: Angola's recurring oil challenges in a new context - Lucy Corkin (The Oxford Institute for Energy Studies, 2017)
Angola is one of Africa's most established petro-states, with initial forays into the country's oil acreage predating national independence. A failure to diversify the economy significantly away from the now well-established oil industry proved disastrous during the global financial crisis of 2008-9: the plunge in oil prices by nearly two thirds from a high of USD147 forced the Angolan government to consider revising the oil benchmark figure in its 2009 budget to below break-even levels. Despite a recovery in the intervening years, Angola is in much the same plight barely a decade later, albeit that this time the low oil price environment is looking more and more likely to be `the new normal', rather than a sudden, dramatic shock. Oil remains the source of approximately 98 per cent of the country's foreign exchange and 75 per cent of government revenue. As such, it is likely that this time around there will be far more wide-ranging consequences for Angola, its oil industry, and the country's major foreign investors, the international oil major (IOCs). This is particularly because the country's two constants, which have represented political and economic stability, namely President Eduardo dos Santos and the ubiquitous role of Sonangol in the economy are about to change.
Keywords: 330; Mineralölwirtschaft; Erdölvorkommen; Förderkonzession; Angola